POLA AKSES PETANI PENGGARAP LAHAN DI KAWASAN PERLUASAN TAMAN NASIONAL GUNUNG GEDE PANGRANGO JAWA BARAT - Arief Sudhartono; Sambas Basuni; Bahrui .; Didik Suharjito (Media Konservasi, 2011)
Nature resource utilization by local peoples around the resource have been part of Indonesian culture, occuring at many places, for instance in expansion area of Gunung Gede Pangrango National Park (TNGGP). Research was directed to describe the access pattern (way of getting access and access utilization forms) in frame on formulating model and strategy of restoration activities implementation. Research result shown that community access interrelated  with history of this area management and dependency of land user to forest resources that is influenced by land property factor, agronomic culture, and local institution; also shown that there are 2 (two) types of community  access goals i.e. non woody forest product harvesting and forest land using as agronomic activity that can be differenced  into 5 sub-types utilization forms base on kind of commodities (main food, horticulture, trees, Multi Purpose Tree specieses, and medicinal crop); 3 sub-tipes base on  time scale of commodities production (seasonal, annual, perenial); and 4 sub-tipes based on agronomic pattern (agronomic system base), i.e: vegetable base, rice-horticulture base, casava-banana base, and agroforestry. Finding 5 kind of access patterns of community to gain access on forest land i.e:  land distribution pattern, self-community inisiative pattern, inheritance pattern, compensation cost pattern, and pawning/rental pattern. Necessarily to formulate institution for ensuring restoration object and community access. Keywords:  access, conflict,Gede Pangrango National Park ,forest resource,restoration.